Forecasting the elimination of active trachoma: An empirical model. - Kristen K Renneker; Paul M Emerson; P J Hooper; Jeremiah M Ngondi (Public Library of Science (PLoS), 2022)
Background Great progress has been made toward the elimination of trachoma as a public-health problem. Mathematical and statistical models have been used to forecast when the program will attain the goal of the elimination of active trachoma, defined as prevalence of trachomatous inflammation-follicular in 1-9 year olds (TF1-9) <5%. Here we use program data to create an empirical model predicting the year of attaining global elimination of TF1-9. Methodology/principal findings We calculated the mean number of years (95% CI) observed for an implementation unit (IU) to move from a baseline TF1-9 prevalence ≥5% to the elimination threshold, based on the region (Ethiopia vs. non-Ethiopia) and baseline prevalence category. Ethiopia IUs had significantly different rates of reaching the TF1-9 elimination threshold after a trachoma impact survey (TIS) compared to non-Ethiopia IUs across all baseline categories. We used those estimates to predict when remaining active trachoma-endemic IUs (TF1-9 ≥5%) would have their last round of mass drug administration (MDA) based on the mean number of years required and number of MDA rounds already completed. Our model predicts that elimination of TF1-9 will be achieved in 2028 in Ethiopia (95% CI: 2026-2033) and 2029 outside of Ethiopia (95% CI: 2023-2034), with some IUs in East Africa predicted to be the last requiring MDA globally. Conclusions/significance Our empirical estimate is similar to those resulting from previous susceptible-infectious-susceptible (SIS) and mathematical models, suggesting that the forecast achievement of TF1-9 elimination is realistic with the caveat that although disease elimination progress can be predicted for most IUs, there is an important minority of IUs that is not declining or has not yet started trachoma elimination activities. These IUs represent an important barrier to the timely global elimination of active trachoma.